Tetramethylpyrazine Enhances the Antitumor Effect of Paclitaxel by Inhibiting Angiogenesis and Inducing Apoptosis - Zou, Liang; Liu, Xiaowei; Li, Jingjing; Li, Wei; Zhang, Lele; Li, Jian; Zhang, Jinming (Frontiers in Pharmacology, 2019)
Recent published findings have demonstrated the effectiveness of combining molecules from traditional Chinese medicine with chemotherapeutic drugs to treat cancer. Combined administration of these agents can overcome drug-mitigating responses as well as reduce adverse side effects, thereby enhancing the efficacy of the therapy. Tetramethylpyrazine (TMP), an alkaloid monomer from the medicinal herb Ligusticum chuanxiong hort, is known to exert a variety of anti-tumor effects including inhibition of tumor cell proliferation, metastasis and drug resistance. In this research, we investigated anti-tumor effects of TMP combined with paclitaxel (PTX), a frontline chemotherapeutic drug, in vitro and in vivo. Our results indicate that TMP enhances the anti-tumor effects of PTX in ovarian cancer A2780 and SKOV3 cells. Furthermore, we found that combined treatment of TMP and PTX suppressed angiogenesis by inhibiting both ERK1/2 and Akt pathways and promoted apoptosis of tumor cells compared to TMP or PTX treatment alone. Moreover, TMP augmented the anti-tumor effects of PTX in ovarian cancer A2780 xenograft mouse models by significantly decreasing tumor burden and partially decreasing the toxicity of PTX, as evidenced by the decreased expression of proliferation and angiogenesis markers as well as the H&E staining and biochemical indexes assay. Overall, our findings provide novel mechanistic insight into the efficacy of combining of potent molecules present in traditional Chinese medicine with chemotherapeutic drugs for therapeutic intervention in cancer.